(untitled) (MUST JOURNAL OF RESEARCH AND DEVELOPMENT, 2025)
The growing environmental burden posed by plastic and mixed-material waste from fast-moving consumer goods (FMCG) packaging has intensified the demand for zero-waste alternatives that balance mechanical performance, sustainability, and cost-effectiveness. This study aims to develop and evaluate a robust, industrial engineering-based decision-support and validation framework for selecting, optimizing, and validating zero-waste packaging materials and geometries The research employs a multi-stage methodology beginning with material screening via Analytic Hierarchy Process (AHP) and Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS), focusing on four key attributes: mechanical strength (40%), environmental performance (30%), cost (20%), and processability (10%). PLA (Polylactic Acid), recycled corrugated cardboard, and sugarcane bagasse emerged as top contenders with PLA receiving a TOPSIS score of 0.826. Finite Element Analysis (FEA) was used to validate structural integrity under a 100 N axial load across different packaging geometries. Multi-objective optimization was performed using NSGA-II to identify Pareto-optimal solutions, balancing compressive strength, unit cost, and global warming potential (GWP). Finally, a Life Cycle Engineering (LCE) framework was applied to assess cradle-to-grave environmental impacts including cumulative energy demand (CED), carbon emissions, eutrophication, and fossil resource depletion. The results show that PLA-based packaging exhibited a compressive strength of 6.1 MPa, maximum von Mises stress of 3.2 MPa, and strain of 0.021, significantly outperforming traditional PET (stress: 7.8 MPa, strain: 0.046) and corn-starch-based composites (stress: 5.9 MPa, strain: 0.047). The optimized PLA packaging unit cost was 0.038, representing a 23% cost reduction compared to molded PET packaging, while achieving a 35.6% reduction in GWP (0.72 kg CO₂-eq). LCE outcomes further revealed 48% lower cumulative energy demand and 41% lower eutrophication potential compared to PET. A novel Sustainability Performance Index (SPI), ranging from 0.42 to 0.88, was used to holistically rank alternatives, with PLA-based reinforced shell structures obtaining the highest SPI due to superior mechanical-environmental trade-offs. These findings demonstrate the viability of integrating decision-support algorithms, mechanical validation, and life cycle modeling to guide industrial transitions toward scalable and zero-waste packaging solutions.